(untitled) (Research, Society and Development, 2021)
The objective of the present work was to present the main challenges and cares during the dental treatment of cancer patients, with emphasis on the care during the endodontic treatment. Methodology: Report of three clinical cases of patients who needed endodontic treatment and were undergoing cancer treatment. Results: Most cancer patients have important dental needs and need detailed care before, during and after cancer therapy. The main purpose of dental treatment in these patients is to stabilize oral conditions to reduce or eliminate the risk of local and systemic infection, as well as to monitor the possible emergence of sequelae resulting from cancer treatment. Conclusion: Endodontic treatment aims to minimize the risk of complications and improve the patient’s quality of life. And the interaction of the dentist with the oncology team in the care and care of the patient undergoing treatment is extremely important in all stages of the disease.